Model of time-dependent and stress-dependent chloride penetration of concrete under sustained axial pressure in the marine environment. (10th May 2018) - Xu, Jun; Li, Fumin; Zhao, Jie; Huang, Lang
Highlights: Relationship between surface chloride concentration, stress and time was developed. Relationship between chloride diffusion coefficient, stress and time was developed. Chloride penetration model for coupled stress level, time was proposed. Abstract: The effect of sustained compressive loading on the chloride penetration of concrete was investigated and a self-monitoring loading device was developed. A series of prisms were loaded under five different sustained axial stress levels and four different numbers of wet/dry chloride cycles. Both the apparent chloride diffusion coefficient D a and the surface chloride concentration C s values were time and stress dependent with a sudden change threshold value of approximately 0.3 f c . A model was proposed to predict the chloride penetration profiles of concrete under sustained axial pressure, taking both the time-dependent and the stress-dependent characteristics of D a and C s into account.